Konsep Makkīyah dan Madanīyah dalam Studi Ḥadīth: Menggagas Pemetaan Kronologis Had?th Nabaw? - Dzikri Nirwana (Islamica: Jurnal Studi Keislaman, 2008)
The Qurānic Studies have long recognized the conceptual dichotomy of Makkīyah and Madanīyah where verses are classified as either belonging to the period of Makkah or Madinah. This paper suggests that this conceptual dichotomy may also be applied in the study of the science of the prophetic saying (hadīth). We propose that paradigm of the Qurānic Studies concerning the periodical distinction may be borrowed to understand and classify the prophetic sayings along the line of Makkīyah and Madanīyah. The paper however acknowledges this effort is not without methodological difficulties. There are hadīth that may ?in terms of their characteristics and substance- be regarded as Makkī, but may also be considered as Madani because they are narrated by the people of Madinah (the Ansār). To tackle this problem, we propose a double-way strategy. We will first find out which hadīths are regarded as Makk? in terms of their characteristics and substance, and then examine the idea of what many have called the ?argumentation of the prophetic term?. The first is about the thematic study, while the second is about the analysis of the term of a hadīth. The first will involve the consultation of mainly the hadīth authoritative book called Miftāh Kunūz al-Sunnah, while the second will consult those books that employ the personal-encyclopedic approach including books of hadīth, the sciences of the Qurān (tafsīr), the reason of revelation (asbāb al-nuzūl), the reason of decreeing (asbāb al-wurūd), and the autobiography of the prophet (sīrah). The meaning of a hadīth and its appropriation in these books will be analyzed in the light of the science of hadīth. The paper will examine how different scientists of tafsir, hadīth, and so on would understand and interpret the same hadīth.